Friedliche Revolution und Religionspädagogik – Bilanz und Plädoyer für einen erweiterten europäischen Referenzrahmen - Käbisch, David (Zeitschrift für Pädagogik und Theologie, 2019)
The term “Peaceful Revolution” (“Friedliche Revolution”) means the process of social, political, and religious change that led to the end of Communist rule 30 years ago in Germany as well as other European countries such as Poland, Czechoslovakia, and Hungary. How did this turning point affect religious education of the time? And how does it affect religious education today? With regard to the papers and interviews in the present journal we argue that the Peaceful Revolution and its relevance for religious education should be examined in a European reference framework. To achieve this, we systematically extend comparative approaches by using the methods of transnational history, such as connected history and global history. Finally, the article lines out didactical consequences of this approach.